Pareto-PageRank algorithm - Tuhkanen, Olli (My University, 2022)
PageRank algorithm is a powerfull graph analysis tools. This algorithm has been used in large variety of different applications. This thesis combines weighted PageRank with multiobjective optimization techniques producing a tool called Pareto-PageRank algorithm. This extension of the original PageRank allows it to be used in more demanding graph vulnerability analyses. This thesis covers the theory behind PageRank and multiobjective optimization. After the theory, the Pareto-PageRank algorithm itself is introduced and it's Python implementation is tested on real world road network data.
Keywords: PageRank, Graph theory, Pareto-efficiency, Vulnerability analysis